Reconfigurable active integrated antenna with log‐periodic matching network structures and reduced PIN diodes for WLAN/WiMAX applications. Issue 4 (April 2016) - Mazloum, Jalil
ABSTRACT: A novel reconfigurable active integrated antenna for WiMAX/WLAN applications is presented. By using a radiating patch with a pair of folded microstrip arms in the active feedback antenna two new resonances can be achieved. Also a novel reconfigurable low noise amplifier (RLNA) with log‐Periodic matching network structures and reduced PIN diode for WiMAX/WLAN applications is presented. By using new design of dual output matching network and reduced pin diode, a novel design of the RLNA is performed. In ordinary way to switch between two frequencies, we need two pin diodes in input matching networks, and two pin diodes in output matching network. But for the first time, in this article by using dual‐band matching network and log‐periodic relationship between matching networks lengths, we reduced number of pin diodes from four to one. By using the [S] parameters of the active element, a novel design of the microwave oscillator is performed. Simulated and experimental results obtained for this antenna show that the proposed Active Integrated Antenna (AIA) has a good return loss and radiation behavior within the WiMAX/WLAN frequency range. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:787–791, 2016